THE EFFECT OF EPS AND PBV ON SHARE PRICES IN BANKING COMPANIES LISTED ON THE IDX - Nuri Maulida; Didin Rasyidin Wahyu; Ombi Romli (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Stock prices reflect a company's value and are an important consideration for investors in making investment decisions. Earnings per share and price influence stock price movements relative to book value. This study was conducted on banking sector companies listed on the Indonesia Stock Exchange during the 2021–2025 period. The purpose of this study was to determine the effect of earnings per share and price-to-book value on stock prices, both partially and simultaneously, in banking sector companies listed on the Indonesia Stock Exchange during the 2021–2025 period. This study employed a quantitative method with an associative approach. The sample was selected using a purposive sampling technique, resulting in 7 companies with 35 observations. The data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. The results showed that earnings per share had a positive and significant effect on stock prices (t = 7.455; Sig. = 0.000). Price-to-book value also had a significant effect (t = 2.600; Sig. = 0.014). Simultaneously, both variables significantly affected stock prices (F = 32.797; Sig. = 0.000). The coefficient of determination (R² = 0.672) indicates that both variables can explain 67.2% of the variation in stock prices. In conclusion, earnings per share and price to book value have a positive and significant effect on stock prices, both partially and simultaneously, in banking sector companies listed on the Indonesia Stock Exchange during the 2021–2025 period.